Effects of long‐acting analogues of lamprey GLP‐1 and paddlefish glucagon on alpha‐ to beta‐cell transdifferentiation in an insulin‐deficient transgenic mouse model. (11th April 2021) - Graham, Galyna V.; Conlon, J. Michael; Moffett, R. Charlotte; Abdel‐Wahab, Yasser H.; Flatt, Peter R.
Abstract : The abilities of the long‐acting, dual‐agonist anti‐diabetic peptides [D‐Ala 2 ]palmitoyl‐lamprey GLP‐1 and [D‐Ser 2 ]palmitoyl‐paddlefish glucagon to induce α‐cell to β‐cell transdifferentiation were investigated in Glu CreERT2 ;ROSA26‐eYFP mice. These animals have been genetically engineered so that yellow fluorescent protein is specifically expressed in glucagon‐producing α‐cells, thereby allowing cell lineage tracing. Insulin deficiency was produced by treatment of the mice with multiple low doses of streptozotocin. Administration of the peptides (twice daily intraperitoneal injections of 25 nmol/kg body weight over 10 days) to streptozotocin‐treated mice produced significant ( P < 0.05) increases in pancreatic insulin content and plasma insulin concentrations compared with control mice. Immunohistochemical studies demonstrated a significant ( P < 0.05) increase in the % of cells staining for both insulin and fluorescent protein in islets located in the head region of the pancreas (from 10.0 ± 1.3% of total cells in untreated mice to 20.0 ± 3.85% in mice treated with D‐Ala 2 ]palmitoyl‐lamprey GLP‐1 and to 17.3 ± 1.1% in mice treated with [D‐Ser 2 ]palmitoyl‐paddlefish glucagon). Corresponding effects upon islets in the tail region were not significant. The data indicate an improvement in β‐cell mass and positive effects on transdifferentiation of glucagon‐producing to insulin‐producing cells. The study provides further evidence that proglucagon‐derived peptides from phylogenetical ancient fish show therapeutic potential for treatment of diabetes. Abstract : Treatment of insulin‐deficient Glu CreERT2 ;ROSA26‐eYFP mice with either [D‐Ala 2 ]palmitoyl‐lamprey GLP‐1 or [D‐Ser 2 ]palmitoyl‐paddlefish glucagon increased the % of cells staining for both insulin and fluorescent protein in islets located in the head region of the pancreas. The data indicate that the peptides promote α‐cell to β‐cell transdifferentiation leading to increased pancreatic insulin content and circulating insulin concentrations.